Scorpionism in Brazil: Space-time approach and risk areas in 2012 to 2024 - Lacerda, Alec Brian; Cândido, Denise; de Azevedo, Thiago Salomão [UNESP]; Wen, Fan Hui; Freitas, Gisele Dias; Dourado, Flávio Santos; Neto, Francisco Chiaravalloti (Public Library of Science (PLoS), 2025)
BACKGROUND: Scorpionism is a neglected public health problem in Brazil and there is currently a significant increase in the number of cases. In Brazil, the Tityus genus is the biggest cause of accidents and increases the risk of death in children under the age of 10. The aim of this study is to identify high and low risk areas for scorpion accidents in Brazil. METHODOLOGY: This is an ecological and descriptive study of the occurrence of scorpionism in Brazil and in high-risk municipalities between 2012 and 2024. The analysis included all 5,570 municipalities of Brazil. Bayesian incidence rates were calculated and standardized by age group and sex. Spatial, space-time, temporal, seasonal and time trend scanning techniques were used to identify high and low risk clusters in Brazilian municipalities. The Gini coefficient function was selected to remove hierarchical clustering detection and to identify the best population percentage (%) for the data sample. Socio-demographic, environmental and climatic variables were chosen and compared between the municipalities within the high and low risk clusters to assess the indicators in different realities. PRINCIPAL FINDINGS: A total of 1,729,023 cases of scorpionism and 1,230 deaths were reported across Brazil's 5,570 municipalities between 2012 and 2024. The incidence rate rose from of 31.8 per 100,000 inhabitants in 2012 to 142.82 per 100,000 inhabitants in 2024 (349% increase). The data shows that more children die and the older adults suffer the most from accidents. The regions of Minas Gerais, São Paulo and Bahia were the areas most affected by scorpionism, with high-risk clusters and an upward trend over time. The northern region showed the opposite pattern. CONCLUSIONS: More studies are needed to understand why these accidents happen in these regions, in order to support policies, surveillance actions and the control and monitoring of this health problem.